What’s the connection? Sarcoidosis and combined variable immunodeficiency: A Single center retrospective case series - MacDowell, Sarah; Singha, Arindam; Crouser, Elliott (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background and aim: Sarcoidosis is a disorder hallmarked by non-caseating granulomas and can involve multi-organ systems but most frequently affects the lungs, eyes, central nervous system, and skin.1 Combined Variable Immunodeficiency (CVID) is a disorder featuring hypogammaglobulinemia, an inadequate response to vaccination, and a history of recurrent bacterial and viral infections, most commonly pneumonia, sinusitis, and ear infections. 2 CVID can also present with non-caseating granulomas, including in Granulomatous Lymphocytic Interstitial Lung Disease (GLILD), making distinguishing between these conditions challenging. There continues to be a debate about how these two conditions are related and what the guidelines should be related to checking quantitative immunoglobulins among those suspected of having sarcoidosis. Methods: This single-center retrospective review was performed at a large midwestern academic center with a large sarcoidosis referral base using available data from the past seventeen years. ICD-9 and ICD-10 codes for CVID and Sarcoidosis were used to identify individuals in billing for outpatient encounters Results: A total of 1920 cases of sarcoidosis and 231 cases of CVID were identified, with eight individuals identified as having both CVID and sarcoidosis diagnoses coded in the same outpatient clinical encounter, which is just 0.042% of the total number of sarcoidosis cases. Conclusions: In place of universal quantitative immunoglobulin screening among those with sarcoidosis, which has additional costs and leads to further challenges with other causes of hypogammaglobulinemia other than CVID, this review points out essential patient features where testing should instead be focused. Identified patient features based on this review that should lead to quantitative immunoglobulin testing include a personal history of recurrent sinopulmonary infections, individual or family history of autoimmune conditions, computed tomography (CT) chest with non-traction-related bronchiectasis, and middle to lower lobe pattern of lung involvement on CT.